Arrhythmogenic right ventricular cardiomyopathy/dysplasia (ARVC/D) in clinical practice. Issue 1 (21st December 2017) - Li, Ka Hou Christien; Bazoukis, George; Liu, Tong; Li, Guangping; Wu, William K. K.; Wong, Sunny Hei; Wong, Wing Tak; Chan, Yat Sun; Wong, Martin C. S.; Wassilew, Katharina; Vassiliou, Vassilios S.; Tse, Gary
Abstract: Arrhythmogenic right ventricular cardiomyopathy/dysplasia (ARVC/D) is an inherited myocardial disease characterized by fibro‐fatty replacement of the right ventricular myocardium, and associated with paroxysmal ventricular arrhythmias and sudden cardiac death (SCD). It is currently the second most common cause of SCD after hypertrophic cardiomyopathy in young people <35 years of age, causing up to 20% of deaths in this patient population. This condition has a male preponderance and is more commonly found in individuals of Italian and Greek descent. To date, there is no single diagnostic test for ARVC/D and the diagnosis is made based on clinical, electrocardiographic, and radiological findings according to the Revised 2010 Task Force Criteria. In this review, we will discuss the mainstay treatment which includes pharmacotherapy, implantable cardioverter‐defibrillator insertion for abortion of sudden cardiac death, and in the advanced stages of the disease cardiac transplantation.